Human development income transfers in the longer term - Armando Barrientos (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
The task for this paper is to provide some reflections on the future role of human development income transfers. Bolsa Família's 10th anniversary provides a timely opportunity, and a fertile setting, to consider this issue. It provides an opportunity for a detailed assessment of the successes and continued challenges associated with a decade of implementation, to take stock of what has been achieved, the way in which barriers and limitations have been overcome, and the new tasks which have come to light. The contributions to this book undertake this assessment.2 The focus of this chapter is on the longer term, on the future role of human development income transfer programmes within the welfare institutions3 emerging in low- and middle-income countries, and especially Latin America. It considers the extent to which a decade of Bolsa Família maps out a route to establishing the long-term institutional framework needed to achieve and sustain the eradication of poverty. This is of considerable importance to low- and middle-income developing countries. Proposals on the post-2015 development agenda have raised the prospect of a commitment by the international community to work towards achieving a zero target for extreme poverty by 2030.4 The sustained fall in global extreme poverty since the 1990s has contributed to raising expectations of what can be achieved in the medium term. The share of the global population living on less than US1.25 a day fell from 43.1 per cent in 1990 to 22.4 per cent in 2008, and the numbers of people in extreme poverty fell from 1.9 billion to 1.2 billion (Ravallion and Chen, 2012). Although the decline in the global incidence of extreme poverty has been dominated by trends in China, the Latin America region shows a strong performance, having reduced US1.25/day poverty from 12.2 per cent in 1990 to 6.5 per cent in 2008, and US2.5/day poverty from 22.4 per cent to 12.4 per cent in the same period. Sustaining a rate of extreme poverty reduction of around 1 per cent a year over the next decade and a half could take us closer to a world free from extreme poverty.
Keywords: 330